Perjanjian Terapeutik Terhadap Pasien Sebelum Dilakukan Pembedahan: Studi Kasus RSUD Biak Numfor - Inosentius Teturan (Kyadiren, 2021)
This study aims to determine the provision of tarapeutic agreement particularly at Biak’s Regional General Hospital. In addition, this study also seeks to determine the legal protection for health workers and patients in therapeutic agreements. This study used a normative-empirical juridical research method where the data sources were available through literature review and also through the process of involved observation and interviews with related parties. The results of this study indicate that Biak’s Regional General Hospital has carried out the therapeutic agreements properly to obtain certainty in legal standing by involving doctors in the therapeutic agreement so that patients also get certainty in legal protection if negligence happens. The doctors also get legal protection from existing regulations. Therefore, legal protection for patients and health workers is clear in accordance with existing regulations such as the Consumer Protection Act, Law no. 23/1992 on Health, and Law No. 29/2004 on Medical Practice.